A produção oral do acadêmico em formação na habilitação do curso de Letra-inglês na Universidade Federal do Amapá (UNIFAP): estudo de caso - PEREIRA, Rogéria Almeida (UNIFAP – Universidade Federal do Amapá, 2022)
In face of the difficulties in the learning process of acquiring a second language it is important to point out the development of the primary abilities (speaking, listening, reading and writing). It is know that the proficient use of a foreign language in social contexts must develop these four abilities. however there is a major problem here and many questions arise about the “how” to do it, “how” provide suitable environments for the development of such skills and even “how” to encourage the learner to develop their autonomy. It is therefore extremely important and extensive subject for the future teaching professionals of foreign language. For not to unfold this work in superficial observations it will focus in only one of these skills: the oral one. The work tried to do a qualitative analysis of how has been taught this ability in the classroom, in the student‟s and Professor‟s view of the English Letters course from The UNIFAP. The choice of corpus analysis was made because the graduating students are ready to practice the profession and it was observed the needing of use the oral abilities in their career. In the context of the research we analyzed two classes of English Letters which are completing graduation and the area professors of English in the Institution researched, using as an analytical tool the semi-structured interview and student and professor‟s recordings as well as documentary analysis.